A QUALITATIVE STUDY OF HEALTH SERVICES COSTING IN INDONESIA - Munandar, Agus (Universitas Aisyah Pringsewu, 2023)
This paper aims to analyze the implementation of health costing in healthcare institution. Most hospitals undertake health cost calculations using different methods such as per diem, case based, or fee for services approaches. This study presents the management’s decision on the costing methodology. This research employed a phenomenological approach to derived conclusions and explain the nature of implementation based on experiences of healthcare staffs. The results of this study indicate that healthcare management considers allocating overhead cost to its services using Activity Based Costing. The management also takes into account some direct costs such as surgery, medical professional, hospital stays, laboratories test, and medication. Furthermore, some hospital management incurs bonding cost to reduce the agency conflict between health professionals and their principals trhough agreement letters.